Oxytocin and Estrogen Receptor β in the Brain: An Overview - Acevedo-Rodriguez, Alexandra; Mani, Shaila K.; Handa, Robert J. (Frontiers in Endocrinology, 2015)
Oxytocin is a neuropeptide synthesized primarily by neurons of the paraventricular and supraoptic nuclei of the hypothalamus. These neurons have axons that project into the posterior pituitary and release oxytocin into the bloodstream to promote labor and lactation; however, oxytocin neurons also project to other brain areas where it plays a role in numerous brain functions. Oxytocin binds to the widely expressed oxytocin receptor, and, in doing so, it regulates homeostatic processes, social recognition and fear conditioning. In addition to these functions, oxytocin decreases neuroendocrine stress signaling and anxiety-related and depression-like behaviors. Steroid hormones differentially modulate stress responses and alter oxytocin receptor expression. In particular, estrogen receptor β activation has been found to both reduce anxiety-related behaviors and increase oxytocin peptide transcription, suggesting a role for oxytocin in this estrogen receptor β mediated anxiolytic effect. Further research is needed to identify modulators of oxytocin signaling and the pathways utilized and to elucidate molecular mechanisms controlling oxytocin expression to allow better therapeutic manipulations of this system in patient populations.